Effects of Schisandra chinensis extract on gastrointestinal motility in mice. (1st July 2015) - Ahn, Tae Seok; Kim, Dae Geon; Hong, Noo Ri; Park, Hyun Soo; Kim, Hyungwoo; Ha, Ki-Tae; Jeon, Ju-Hong; So, Insuk; Kim, Byung Joo
Abstract: Ethnopharmacological relevance: Schisandra chinensis (Turcz.) Baill. (SC) continues to be used as a traditional folk medicine in Asia, especially for the treatment of gastrointestinal (GI) disorders related to gastritis, diarrhea, enterocolitis and abnormal GI motility. Aim of the study: Because GI disorders, especially abnormal GI motility, are major lifelong problems, we investigated the effects of SC on the pacemaker activity of the interstitial cells of Cajal (ICCs) in murine small intestine and GI motility. Materials and Methods: Enzymatic digestions were used to dissociate ICCs from small intestines, and the whole-cell patch-clamp configuration was used to record potentials generated by cultured ICCs. In vivo effects of SC on GI motility were investigated by measuring the intestinal transit rate (ITR) of Evans blue in normal and GI motility dysfunction mice. Results: SC extracts depolarized the membrane potentials of ICCs in a dose dependent manner. Pretreatment with Ca 2+ free solution or thapsigargin (a Ca 2+ -ATPase inhibitor in the endoplasmic reticulum) abolished the generation of pacemaker potentials by ICCs, and under these conditions, SC extract did not depolarize the membrane potentials of ICCs. In addition, membrane depolarizations were inhibited by intracellular GDPβ S and by U-73122 (an active phospholipase C (PLC) inhibitor). In normal mice, ITRs were significantly increased by SC extract (0.1–1 g/kg, intragastrically (i.g.)) in a dose dependent manner. Also, SC extract significantly recovered the GI motility dysfunctions in acetic acid (AA)-injected and streptozotocin (STZ)-induced diabetic mice, which are the GI motility animal models. Materials and methods: SC extract modulates pacemaker potentials in ICCs in a dose dependent manner via external and internal Ca 2+ regulations, and via G protein and the PLC pathway. In addition, SC extract increased ITRs in normal and abnormal GI motility mice models. This study shows that SC extract offers a basis for the development of a prokinetic agent that prevents or alleviates GI motility dysfunctions. Graphical abstract: